2015
DOI: 10.3997/2214-4609.201412134
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Permeability on Foam-model Parameters and the Limiting Capillary Pressure

Abstract: SUMMARYAccurate modelling of foam rheology on the field scale requires detailed understanding of the correlation between the fundamental properties of foam and the scalable parameters of the porous medium. It has been experimentally observed that foam experiences an abrupt coalescence when the capillary pressure in the porous medium approaches a certain value referred to as the "limiting capillary pressure", Pc*. Current foam models that treat foam texture implicitly mimic this fundamental behaviour with a so-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In foam displacement experiments in porous medium, as gas saturation increases, capillary pressure also increases until it reaches a certain point called the limiting capillary pressure, beyond which the foam films start to break and become coarser in texture. 37 It has been observed that as foam quality increases and water saturation decreases correspondingly, there reaches a value of S w below which the coalescence of foam occurs and it starts drying up, thus becoming coarser in texture. 37 The capillary pressure corresponding to this water saturation value as mentioned earlier is known as limiting capillary pressure.…”
Section: Energy and Fuelsmentioning
confidence: 99%
See 3 more Smart Citations
“…In foam displacement experiments in porous medium, as gas saturation increases, capillary pressure also increases until it reaches a certain point called the limiting capillary pressure, beyond which the foam films start to break and become coarser in texture. 37 It has been observed that as foam quality increases and water saturation decreases correspondingly, there reaches a value of S w below which the coalescence of foam occurs and it starts drying up, thus becoming coarser in texture. 37 The capillary pressure corresponding to this water saturation value as mentioned earlier is known as limiting capillary pressure.…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…37 It has been observed that as foam quality increases and water saturation decreases correspondingly, there reaches a value of S w below which the coalescence of foam occurs and it starts drying up, thus becoming coarser in texture. 37 The capillary pressure corresponding to this water saturation value as mentioned earlier is known as limiting capillary pressure. It must be noted that if the foam collapse is abrupt then the transition region between high and low quality regime occurs at one particular value of water saturation which is represented as S w *.…”
Section: Energy and Fuelsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that finer-textured foam led to larger flow resistance [39][40][41]. Some foam flow models have been proposed to simulate foam flow and reveal the blocking mechanism [42][43][44][45][46]. There was one thing in common in all models that foam texture was considered to be a determining factor for foam flow behavior.…”
Section: Introductionmentioning
confidence: 99%